ESL medical students’ oral proficiency— do they need help? - Abdul Malik, Faridah; Othman, Khairiah (American Scientific Publishers, 2018)
English proficiency is no longer a choice but a tool for survival for medical students who wish to practise medicine in the global working environment of today. Of the many skills that they are required to master, oral communication skills are of paramount importance. The pressure on medical students to interact effectively in oral form is immense in addition to the need to be knowledgeable on the content. Inability to converse well in English has important implications for their learning and could lead to clinically sub-par medical graduates in the future. This study investigates the importance of English oral skills for studies and future career as perceived by the clinical students and to assess the extent of problems that they faced when trying to communicate with their peers, subordinates and superiors especially in the formative clinical years. The data were collected via a structured questionnaire administered to 256 medical students who were in their clinical years. The findings of this study can act as a set of guidelines to be considered when developing programmes to enhance the English oral skills of these medical students.